Dynamics of Lateral Habenula-Ventral Tegmental Area Microcircuit on Pain-Related Cognitive Dysfunctions - Ana Raquel Pereira; Mobina Alemi; Mariana Cerqueira-Nunes; Clara Monteiro; Vasco Galhardo; Helder Cardoso-Cruz (MDPI AG, 2023)
Chronic pain is a health problem that affects the ability to work and perform other activities, and it generally worsens over time. Understanding the complex pain interaction with brain circuits could help predict which patients are at risk of developing central dysfunctions. Increasing evidence from preclinical and clinical studies suggests that aberrant activity of the lateral habenula (LHb) is associated with depressive symptoms characterized by excessive negative focus, leading to high-level cognitive dysfunctions. The primary output region of the LHb is the ventral tegmental area (VTA), through a bidirectional connection. Recently, there has been growing interest in the complex interactions between the LHb and VTA, particularly regarding their crucial roles in behavior regulation and their potential involvement in the pathological impact of chronic pain on cognitive functions. In this review, we briefly discuss the structural and functional roles of the LHb-VTA microcircuit and their impact on cognition and mood disorders in order to support future studies addressing brain plasticity during chronic pain conditions.